Antimycobacterial agents : a study of Liposomal-Encapsulation, comparitive permeability of bronchial tissue and in vitro activity against mycobacterium tuberculosis isolates - Van Rensburg, Lyne (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2012.